Analisis Pengelolaan Keuangan Daerah Pemerintah Daerah Kabupaten Kepulauan Talaud - Pareda, Marlin; Sondakh, Jullie J; Ilat, Ventje (Universitas Sam Ratulangi, 2017)
Abstract. The Regional Budget (APBD) is established to improve the capacity of local government in providing services to the community. The Regional Budget (APBD) is an annual form of the Regional Long-Term Development Plan (RPJPD) as well as the Regional Medium-Term Development Plan (RPJMD) are set up in accordance to the vision and mission of the regional head. The Regional Budget (APBD) is prepared by the Regional Government, discussed and approved by the Regional House of Representatives (DPRD). It is thus becoming a legal product, in form of Regional Regulation (Perda) and must be followed by all institutions in the region. This study aims to analyze the financial management of the Regional Government of Talaud Islands Regency. This is a qualitative exploratory research. Data were obtained through in-depth interviews and documentation studies. Key informants are determined by purposive sampling to obtain accurate information. Interviews were conducted by using semi-structured in-depth interviews. The triangulation method was used in order to test the validity or credibility of data and data sources. Results showed that in the process of local government financial management from planning and budgeting and implementation process has been referring to Permendagri No. 13 of 2006 on Guidelines for Management of regional finances but there are still obstacles that are 1) Bureaucratic Structure, (2) Resources, (3) Communication, (4) Disposition or Attitude, (5) Budget Limitations. Keywords: Regional Financial Management, Obstacles.Abstrak. Dalam meningkatkan kapasitas pemerintah daerah dalam memberikan pelayanan kepada masyarakat maka disusunlah Anggaran Pendapatan dan Belanja Daerah (APBD). Anggaran Pendapatan danÂ Belanja Daerah (APBD) merupakan wujud tahunan dari Rencana Pembangunan Jangka Panjang Daerah (RPJPD) serta Rencana Pembangunan Jangka Menengah Daerah (RPJMD) yang dibuat dari visi dan misi kepala daerah. Anggaran Pendapatan dan Belanja Daerah (APBD) dipersiapkan oleh Pemerintah Daerah, dibahas dan disetujui oleh Dewan Perwakilan Rakyat Daerah (DPRD) sehingga pada akhirnya menjadi produk hukum berupa Peraturan Daerah (Perda) yang harus diikuti oleh segenap lembaga di daerah. Penelitian ini bertujuan menganalisis pengelolaan keuangan daerah Pemerintah Daerah Kabupaten Kepulauan Talaud. Metode penelitian menggunakan kualitatif dengan pendekatan eksploratif. Data diperoleh melalui teknik wawancara mendalam dan studi dokumentasi. Informan kunci ditentukan secara purposive sampling untuk mendapatkan hasil informasi yang tepat dan akurat. Wawancara menggunakan In-depth interview jenis semi terstruktur. Metode triangulasi digunakan dalam pengujian validitas atau kredibilitas data dan sumber data. Hasil penelitian menunjukkan bahwa dalam proses pengelolaan keuangan daerah pemerintah daerah mulai dari proses perencanaan dan penganggaran dan pelaksanaan dilaksanakan berdasarkan ketentuan dalam Peraturan Menteri Dalam Negeri Nomor 13 Tahun 2006 tentang Pedoman Pengelolaan Keuangan Daerah belum optimal masih terdapat hambatan-hambatan yaitu 1) Struktur Birokrasi, (2) Sumber Daya, (3) Komunikasi, (4) Disposisi atau Sikap, (5) Keterbatasan Anggaran.Kata Kunci: Pengelolaan Keuangan Daerah, Hambatan.